(untitled) (The South East European Journal of Economics and Business, 2026)
This study examines how seven dimensions of perceived risk interact to shape purchase intention in cross-border e-commerce (CBEC). Using survey data from 400 Hungarian CBEC users, the study applies a dual method approach combining PLS-SEM and fuzzy-set qualitative comparative analysis (fsQCA). SEM results indicate that fraud risk and information risk exert significant negative net effects on purchase intention. However, fsQCA reveals multiple sufficient configurations, demonstrating that privacy risk and process & time loss risk become critical when combined with high fraud and information risk. The finding highlights that certain risk dimensions are configurationally important despite being statistically insignificant in linear models. By distinguishing between net and configurational effects, this study advances the multidimensional theory of perceived risk and provides actionable insights for SMEs prioritizing risk mitigation in cross-border markets.